“Merariq Syar’i” di Lombok: Studi Living Hadis di Dusun Lendang Simbe - Salimudin Salimudin (UIN Sunan Kalijaga Yogyakarta, 2014)
This study discusses one of the topics in Living Hadits found in Merariq (Marriage) tradition in Dusun Lendang Simbe. The case indicates the instance of various interpretations and Muslim society’s receptive mode of Hadits. In this vein, Hadits has not been only served as books and readings; it could be managed as ‘driving force’ in a broader understanding and tolerance. It seems that the Sasak Muslim could mingle the positionality of Islam in the face of cultural aspect. The study shows that Muslims lived in Lendang Simbe following the command of ‘Tuan Guru’ to avoid the tradition of ‘bebait’ (kidnapping). In the case of ‘nyongkolan’ tradition, they still preserved it with a little modification on the outfits without diminishing the Sasak’s value and meaning.